WOMEN IN FRENCH REVOLUTION: THE KNITTING WOMEN AND THE REIGN OF TERROR - Sreeparvathi. D; Rincy T P (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The French Revolution was one which happened between 1789 and 1799, and which influenced France’s history as well as world history. This revolution first started against the Bourbon dynasty that ruled France. In France, society was chiefly divided into three categories: The First Estate that included the clergy, the Second Estate which comprised the landowners, and the Third Estate which consisted of common people. Of these, while the burden of tax fell completely on the ordinary people of the third estate, the other two categories enjoyed many privileges just like the royal family. The common man had to pay tax to the lords and the clergy. The wars during the reign of Louis XVI had adversely affected the economy of France. Excessive tax burden, poverty, joblessness etc. created discontent in the people. The dawn of an educated middle- class section marked the beginning of the spread of new ideas. The ideas of Voltaire, Rosseau, and Montesquieu led to decentralisation of power, democracy, and the spread of ideas like liberty, equality, and fraternity.